Les droits du mineur en vertu de la Partie VI de la Loi régissant les sociétés commerciales canadiennes - Demers, Robert (Les Cahiers de droit, 1980)
Transfers of shares in the private law of the Province of Quebec raise numerous questions. The rights of the bona fide transferee for value are not clearly settled by the Civil Code and the provincial Companies Act is silent on the issue. In the first part of this article, the author deals with the state of the civil law on the question, illustrating the discussion with a study of the rights of a minor to proceed against bona fide transferees generally and more specifically, under articles 297 and 1487 C.C. In the second part of the article, the question is viewed from the point of view of the federal legislation. Part VI of the Canada Business Corporations Act is studied in detail in so far as the rights of the minor are modified by the statute. This useful exercise indicates clearly the preference given by the federal Act to bona fide purchasers of securities and the rather precarious position of the true owner in questions of conflicting claims. Viewed from a larger perspective, this study reveals an important trend in recent legislative enactments : where traditional rules tend to protect property rights (nemo dat...), contemporary legislations seem to favour unduly the security of commercial transactions.